2013
DOI: 10.1007/s00220-013-1711-4
|View full text |Cite
|
Sign up to set email alerts
|

Wave Decoherence for the Random Schrödinger Equation with Long-Range Correlations

Abstract: In this paper, we study the loss of coherence of a wave propagating according to the Schrödinger equation with a time-dependent random potential. The random potential is assumed to have slowly decaying correlations. The main tool to analyze the decoherence phenomena is a properly rescaled Wigner transform of the solution of the random Schrödinger equation. We exhibit anomalous wave decoherence effects at different propagation scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…10 Proof of estimate (21) We use here the notation of sections 1 and 3. The core of the proof is the following lemma:…”
Section: Proof Of Theorem 21mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Proof of estimate (21) We use here the notation of sections 1 and 3. The core of the proof is the following lemma:…”
Section: Proof Of Theorem 21mentioning
confidence: 99%
“…It is not always the case in practice, as is pointed out in [12,23,31] for geophysical problems, wave propagation in turbulent atmosphere, or medical imaging. This has then stimulated recent mathematical works on wave propagation in random media with long-range dependence [2,18,20,21,22,25,26]. It is shown there that the wave dynamics in such media can be in great contrast with that of waves in media with rapidly decaying correlations.…”
Section: Introductionmentioning
confidence: 99%
“…In order to be efficient, imaging and communication algorithms require insight about how the wave is affected by the rough medium fluctuations. In view of its potential for applications, mathematical description of wave propagation in multiscale random media with long-range correlations has attracted a lot of interest over the last decade [3,11,14,15,17,18,21].…”
Section: Introductionmentioning
confidence: 99%
“…Multiscale random medium with long-range correlations produce stochastic effects on the waves which are very different from the ones produced by perturbations varying on a well defined microscale and with mixing properties [9]. Wave propagation in random media with long-range correlations has already been considered in one-dimensional propagation media [11,18] or open media under the paraxial approximation [3,7,8,14,15]. In these contexts, it has been observed that stochastic effects appear at different propagation scales, all the stochastic effects do not appear at the same time, which is in contrast with perturbations with mixing properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation